The Impact of Psychological Capital On Nurse’s Performance: The Mediating Role of Psychological Well-Being and Work-Family Conflict - Wahyuningsih, Dwi; Wulansari, Nury Ariani (Management Analysis Journal, 2016)
The purpose of this research is to exam the influence of psychological capital, psychological well-being, and work-family conflict on nurse’s performance directly or indirectly that mediated by psychological well-being, and work-family conflict. Data was collected from 99 nurse inpatient care installation Rumah Sakit Umum Daerah Ungaran by giving questionnaire. They were analyzed by using partial and path test in deciding the connection between variables in this study. The result of this study indicated that there was a significant positive effect on psychological capital and psychological well-being toward job performance, also psychological capital toward psychological well-being. The result also indicated that psychological well-being and work-family conflict mediate the effect of psychological capital toward nurse’s performance. While, the effect work-family conflict toward nurse’s performance, work-family conflict toward psychological well-being, and the effect of psychological capital toward work-family conflict showed negative result but there were no significant. In conclusion, this study proved that to increase their performance, the nurses must have psychological capital and psychological well-being. Also, the nurses must be managing their work-family conflict.